Preparation of camellia oil oleogel and its application in an ice cream system. (1st November 2022) - Jing, Xinyu; Chen, Zihan; Tang, Zonghui; Tao, Yuting; Huang, Qiuye; Wu, Yisu; Zhang, Haiwei; Li, Xueling; Liang, Jin; Liu, Zhengquan; Cai, Huimei; Xiao, Hang; et al.
Abstract: This research explored the use of oleogel which was comprised of camellia oil instead of solid fat in ice cream, and not only optimized the process of oleogel ice cream production by single factor response surface experiment, but also characterized it. By comparing oleogel ice cream to two ice creams (camellia oil ice cream and butter ice cream), the results showed that the overrun rate of oleogel ice cream was higher than camellia oil ice cream, and the melting rate was lower than that of butter ice cream. Besides, the hardness of camellia oleogel ice cream was moderate, and the first dropping time of oleogel ice cream was no significant difference with the butter ice creams, whereas longer than that of camellia oil ice cream. Both the viscosity and fat globule instability of the oleogel ice cream was the highest. The unsaturated fatty acids (UFA) content of the oleogel ice cream was significantly increased compared with the butter ice cream. Overall, the comprehensive properties of oleogel ice cream were the best. This research expanded the application of oil gel and provided a reference for the development of ice cream products. Graphical abstract: Image 1 Highlights: The optimum processing parameters of oleogel ice cream were determined. The fatty acids in oleogel ice cream were mainly unsaturated fatty acids. The overall quality of oleogel ice cream was improved. The sensory features of oleogel ice cream was readily acceptable.